IJCM_347A: The relation of Academic motivation with academic stress, self-efficacy and social support among the Paramedical students of tertiary health centre of Uttarakhand- Cross sectional study - Adhikari Ritu; Singh Surendra; Bartwal Janki; Rawat CMS (Wolters Kluwer Medknow Publications, 2024)
Background: Students experiencing academic stress undergo mental distress in anticipation of academic challenges and academic failure, which eventually impacts their studies, interpersonal relationships, and overall well-being therefore academic motivation is essential to continue their studies. Objective: I. To assess the Sociodemographic profile of paramedical students. II. To find correlation between the academic motivation, academic stress, self-efficacy, social support of paramedical students. Methodology: A cross sectional study was conducted over period of 3months after complete enumeration of Paramedical students of Veer Chandra Singh Garhwali Government Institute Of Medical Science & Research, Uttarakhand. Prestructured validated questionnaire of Academic Motivation Scale (ASM- C28) with Cronbachs alpha 0.92, General Self - Efficacy Scale(GSE) with Cronbachs alpha 0.9, Multidimensional Scale of Perceived Social Support(MSPSS) with Cronbachs alpha 0.9 in addition to adapted questions of academic stress was used. Results: 46% of students agree that college education helps them prepare a better career.58% of students feels academic stress while studying Conclusion: Most of the students are academically motivated.